Feasibility of a Modified Otago Exercise Program for Older Adults With Cognitive Vulnerability. (July 2023) - Mangione, Kathleen K.; Darreff, Hope; Welsh, McKenna; Ni, Weihong; Wolff, Edward; Booth, Julie T.; Glenney, Susan S.; Fortinsky, Richard H.
Cognitive vulnerability, that is, clinically significant symptoms of dementia, depression, or delirium, puts older adults at high risk for physical inactivity and falls. Programs addressing activity and falls are needed. The purpose was to determine feasibility of an in-home, modified, Otago Exercise Program (OEP) for those with cognitive vulnerability, based on acceptability (retention and adherence), safety (pain intensity and falls), and potential positive effects (change in short physical performance battery (SPPB)). This secondary analysis of a randomized controlled trial included 80 participants who received the OEP; 64 completed it, 48% had depression, 22% had dementia, and 30% had a combination dementia/depression/delirium. Adherence to home exercise was low to moderate; pain was stable over 16 weeks; 31% of participants reported falls unrelated to OEP. SPPB increased from 6.95 to 7.74 ( p < .01); age by time and diagnosis by time interactions were not significant. The modified OEP shows promising feasibility for older adults with cognitive vulnerability.